Nová a starsí farmaka ovlivnující inzulinovou sekreci - Olsovský, J (Vnitrni lekarstvi, 2009)
The author briefly recapitulates the physiology of insulin secretion and pathophysiology with type II diabetes mellitus. Besides sulfonylurea secretagogues and glinides practically used in the long term, the author points out new possibilities of influencing insulin secretion by way of incretin mimetics and gliptins.
Keywords: diabetes mellitus 2. typu; inzulin; Sulfonylurea Compounds; Glucagon-Like Peptide 1; lidé; sulfonylmočovinové sloučeniny; Insulin Secretion; Humans; Glucose; inkretiny; Insulin; Diabetes Mellitus, Type 2; Incretins; glukagonu podobný peptid 1; sekrece inzulinu; glukosa